Carrot and stick?: the role of financial market intermediaries in corporate social performance - Slager, Rieneke; Chapple, Wendy (Sage, 2016)
his article examines the role of intermediaries in financial markets in fostering corporate sustainability. Responsible investment (RI) indices have been primarily identified as intermediaries that provide information regarding corporate social performance (CSP) for investors and other stakeholders. The authors argue that the role of these intermediaries is not confined solely to information provision, but they may also incentivize high levels of CSP through mechanisms such as exclusion threats, signaling, and engagement. The authors rely on unique access to the archives of the FTSE4Good Index to examine the effects of these mechanisms on CSP. The study shows that companies facing exclusion threats and signaling are more likely to comply with the intermediary’s criteria, and medium levels of engagement leads to higher levels of CSP. The authors contribute to the study of sustainability in financial markets by explicating the mechanisms that intermediaries and other financial actors could employ to foster greater corporate sustainability.